Comprehensive Assessment of Male Lower Urinary Tract Symptoms at a Tertiary Care Urology Clinic: A Prospective Study - Balagobi, B.; Thangarajah, B.R.; Sarma, S.T.; Coonghe, P.A.D.; Sripandurangana, R.; Sivashankar, M.; Gobishangar, S.; Jothini, T.; Sangeetha, U.; Shathana, P. (The College of Surgeons of Sri Lanka, 2024)
Introduction: Lower Urinary Tract Symptoms (LUTS) significantly impact men's quality of life, often due to benign prostatic occlusion. Therefore, the study aimed to assess the severity of LUTS associated with demographic and clinical factors. There is potential for tailored care and public health strategies to alleviate the burden of male LUTS (mLUTS). Methods: A one-year prospective cross-sectional study conducted at a urological clinic in a tertiary care centre, gathered data from male patients using self-reported questionnaires and investigator interviews on Lower Urinary Tract Symptoms and International Prostate Symptoms Score (IPSS). Statistical analysis, employing SPSS, utilized descriptive statistics and the Chi-square test, with significance set at P < 0.05. Results: The total of 181 male patients participated in this study with mean age 66.65 years. The majority (80.7%) were over 60 , showing a mean IPSS score of 21.06 ± 7.8. BMI analysis revealed 58.6% normal and 41.4% overweight/obese, with distinct IPSS scores. Occupation significantly linked to LUTS severity (p=0.002), distinguishing employed and retired individuals. diabetes (p=0.047) and alcohol consumption (p=0.034) were significantly associated with LUTS severity. 44.2% had equally dominant voiding and storage symptoms, and 52.5% underwent surgical interventions, TURP being the most common (30.9%). Moderate and severe LUTS were associated with poor Quality of Life (p=0.0001) Conclusions: mLUTS associated with rising age (more mLUTS in >60 years), obesity/ over weight, Diabetes and Alcohol consumption. Majority had moderated LUTS (IPSS) Study on individuals over 60 found occupation, diabetes, and alcohol consumption linked to severe Lower Urinary Tract Symptoms (LUTS). Coexistence of voiding and storage symptoms underscored complexity. High rates of medical interventions, notably Transurethral Resection of the Prostate, emphasized clinical impact and management challenges in this demographic.
Keywords: Lower urinary tract symptoms; Benign prostatic obstructions; Quality of life; International prostate symptoms score